Creating expert patients: outcomes from a national digital therapeutic approach for people with asthma in Wales - Simon M. Barry; Julian Forton; Gareth R. Davies; Gwyneth A. Davies; Katie Pink; Alison Whittaker; Jerome Donagh; Dan Menzies; Mark Andrews; Grace Moore; Chris Davies (npj Primary Care Respiratory Medicine)
Abstract National applications (apps) for adults with asthma were implemented as part of a respiratory toolkit across Wales from 2020. Data were collected on patient recorded asthma control including the Royal College of Physicians three questions. All general practices in Wales had patients registered on the asthma app and by September 2024, 12,567 (57.8%) of patients who downloaded the app went on to register. Analysis comparing baseline with four or more months of app use demonstrated improvements in the percent of those having a Royal College of Physicians asthma score of 0 (26.5% vs 40.7%, p = 0.0011), together with improvements in those not using a reliever inhaler at all (29.1% vs 39.2%, p = 0.0001). Where we had paired data one year apart, the improvements in asthma control were greater in those from most deprived areas. For those who used the app there were improvements across important metrics of asthma control consistent with better patient self-management.